Partial Cranial Cruciate Ligament Tears Treated with Stem Cell and Platelet-Rich Plasma Combination Therapy in 36 Dogs: A Retrospective Study - Canapp, Sherman O.; Leasure, Christopher S.; Cox, Catherine; Ibrahim, Victor; Carr, Brittany J. (Frontiers in Veterinary Science, 2016)
Objective: To evaluate outcomes in 36 dogs with a partial CCL tear treated with autologous bone marrow aspirate concentrate (BMAC) or adipose derived progenitor cells (ADPC) with platelet rich plasma (PRP) combination. Materials and Methods: Medical records of client-owned dogs diagnosed with an early partial (≤50%) tear of the craniomedial band of the CCL that were treated with BMAC-PRP or ADPC-PRP were reviewed from 2010-2015. Signalment, medical history, physical and orthopedic examination, objective temporospatial gait analyses, radiographs, day 0 and day 90 diagnostic arthroscopy findings, treatment, and outcome were among the data collected. A functional owner questionnaire, including the validated Helsinki chronic pain index (HCPI), was sent to owners whose dog was known to not have had a TPLO. Statistical analysis was performed on data, where significance was established at p<0.05. Results: Stifle arthroscopy findings at 90 days post treatment were available on 13 of the 36 dogs. In 9 dogs, a fully intact CCL with marked neovascularization and a normal fiber pattern was found with all previous regions of disruption healed. One dog revealed significant improvement and received an additional injection. The remaining 3 dogs had a >50% CCL tear and a TPLO was performed. Four additional dogs were known to have had a TPLO performed elsewhere. Baseline and day 90 post treatment objective gait analyses were available on 11 of the 36 dogs. A significant difference was found between the treated limb TPI% at day 0 and day 90 (p=0.0124), and between the treated limb and contralateral limb TPI% at day 0 (p=0.0003). No significant difference was found between the treated limb and contralateral limb TPI% at day 90 (p=0.7466). Twelve questionnaires were returned, of which 8 were performance/sporting dogs. Seven of the 8 had returned to sport; the remaining dog had just begun a return to sport conditioning program 6 months post treatment. All 12 respondents believed their dog had an excellent or very good quality of life, and rated their dog’s procedural outcome as excellent or good. Conclusion: The use of BMAC-PRP and ADPC-PRP shows promise for the treatment of early partial CCL tears in dogs.